2015
DOI: 10.1021/bk-2015-1196.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Surface Photochemistry of Quantum Dot-Porphyrin Nanoassemblies for Singlet Oxygen Generation

Abstract: This Chapter covers the basics of nanotechnology, focusing on hybrid organic-inorganic nanoassemblies based on self-assembly principles. Here, we are willing to discuss the formation principles and mechanisms of excitation energy relaxation being studied for nanoassemblies based on core/shell CdSe(ZnS) colloidal semiconductor quantum dots (QD) exhibiting size-dependent photophysical properties and surfacely activated by pyridyl-substituted porphyrins, H 2 P (bulk solutions) in liquid solvents at 295 K (steady-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 154 publications
(248 reference statements)
0
4
0
Order By: Relevance
“…At first glance all these data are consistent with highly efficient Förster resonant energy transfer (FRET) from QDs to MB molecules which supposed to be main mechanism of enhancing photodynamic properties of various photosensitizers using this approach. [6][7][8] However, upon the inspection of extends of PL quenching and reduction of PL lifetime we have concluded that, for this system, photoinduced charge transfer is the most likely mechanism of PL quenching. The evidence for the photoinduction can be derived through the comparison of lifetime and PL intensity Stern-Volmer plots, which shows orders of magnitude difference (Figure 2d).…”
Section: Methodsmentioning
confidence: 87%
“…At first glance all these data are consistent with highly efficient Förster resonant energy transfer (FRET) from QDs to MB molecules which supposed to be main mechanism of enhancing photodynamic properties of various photosensitizers using this approach. [6][7][8] However, upon the inspection of extends of PL quenching and reduction of PL lifetime we have concluded that, for this system, photoinduced charge transfer is the most likely mechanism of PL quenching. The evidence for the photoinduction can be derived through the comparison of lifetime and PL intensity Stern-Volmer plots, which shows orders of magnitude difference (Figure 2d).…”
Section: Methodsmentioning
confidence: 87%
“…In this case, like for multiporphyrin complexes (described above), a controllable formation of "QD-Porphyrin" nanoassemblies have been realized as a surface passivation of CdSe/ZnS ODs by tetrameso-pyridyl substituted porphyrins (free base and/or Cu-complex) in titration experiments. [29,[90][91][92][93][94][95][96][97][98][99] It is well-known from chemical background that the 3d transition metal Zn 2+ ion (of ZnS shell) has empty 3d 10 orbital while heteroatom N-pyr of the porphyrin mesopyridyl ring is a very good e-donor having an unshared electron pair. Thus, in this case a "key-lock" principle is realized via oneor two-fold non-covalent coordination Zn….N-pyr.…”
Section: Methodsmentioning
confidence: 99%
“…[29,[90][91][92][93][94][95][96][97][98][99]123] Structures of QDs and porphyrin molecules as well as necessary details explaining the formation of nanoassemblies "QD-Porphyrin" are shown in Figure 9. The results described below concern to the analysis of the interaction between semiconductor CdSe/ZnS quantum dots and surface attached porphyrin molecules (free base and Cu-complex) in order to evaluate the influence of tetrapyrrolic macrocycle on pathways and mechanisms of exciton relaxation in "QD -Cu-porphyrin" nanoassemblies.…”
Section: Tuning Electronic States Of Cdse/zns Quantum Dot By One Cu-pmentioning
confidence: 99%
See 1 more Smart Citation